Land-use conflicts and the sharing of resources between urban and agricultural activities in the Greater Paris Region Results based on information provided by the daily regional press - André Torre; Segolene Darly (European Regional Science Association (ERSA), 2010)
Empirical observation of the forms of agriculture developing at the periphery of cities reveals the generalized presence of particular types of production or commercialisation, which explains why certain sectors, such as the vegetable growing industry or the proximate agricultural productions, are sometimes called "peri-urban agro-industries ". Given this finding, most in the scientific community agree that the specificity of the peri-urban sectors of agricultural production remains to be demonstrated, but that the specific nature of peri-urban land itself is undeniable. Its specificity lies in the fact that an increasing number of users compete for access to resources and land that are traditionally reserved for agriculture. In areas where available resources are limited, the strong competition between the uses that consume these resources causes increasing conflicts and tensions. This is true in the case of agri-urban resources, which in peri-urban areas, are coveted by a diversity of users that perform different, often antagonistic activities. The spatial expansion of cities is, indeed, a process that consumes natural, agricultural or forestland and that generates nuisances and pollutants transmitted through certain "mobile" resources such as water or air. The analyses presented in this article respond to three research objectives: - Identify the objects and resources the uses of which are regulated through conflictual processes - Evaluate the scales of action implemented by the local actors according to the space related issues from which conflict arises - Highlight the socio-economic situations that combine the spatial and social conditions that are conducive to the actors' engaging in conflict. For this purpose, we have performed a quantitative inventory of the conflicts related to the use of agri-urban resources, located within the Greater Paris Region. The first section of this paper presents the geographical context, the conceptual framework and the inventory method we have used. The results of the inventory and the analysis of the data are detailed in the second section, in which they are presented according to the three research objectives we have set for ourselves.
Keywords: 330